2005
DOI: 10.2174/1570163054866882
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Covalent Chemistry in Drug Delivery

Abstract: The targeting of drugs specifically to their sites of action is an important strategy for increasing drug efficacy. Chemists have come up with many elegant schemes that aim to convert drugs into magic bullets. This review focuses on the chemistry that underlies these schemes, with particular emphasis on two types of cleavable covalent bonds that are frequently used to link drugs to their various carriers: disulfide bonds and hydrazone bonds. These linkages have been used to release drugs under specific conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 117 publications
(184 reference statements)
3
112
1
Order By: Relevance
“…The lower pH of the endo-lysosome system has also been used as an intracellular trigger for cleavage of hydrazone linkers. 13,15 To confirm that these conjugates are not cleaved by a physiological pH trigger, the conjugates were incubated in buffer at pH 7.4, 6, and 5 for 18 hr at 37 C. HR-SEC analysis showed no change in the chromatographs at either of the pH conditions tested for all three conjugates (data not shown). These in vitro cleavage studies showed that the HYN conjugate was not cleaved by either a reduction (GSH) or a pH trigger and it is therefore a suitable stable control conjugate.…”
Section: Cleavability Of Conjugatesmentioning
confidence: 96%
See 2 more Smart Citations
“…The lower pH of the endo-lysosome system has also been used as an intracellular trigger for cleavage of hydrazone linkers. 13,15 To confirm that these conjugates are not cleaved by a physiological pH trigger, the conjugates were incubated in buffer at pH 7.4, 6, and 5 for 18 hr at 37 C. HR-SEC analysis showed no change in the chromatographs at either of the pH conditions tested for all three conjugates (data not shown). These in vitro cleavage studies showed that the HYN conjugate was not cleaved by either a reduction (GSH) or a pH trigger and it is therefore a suitable stable control conjugate.…”
Section: Cleavability Of Conjugatesmentioning
confidence: 96%
“…In order to achieve targeted release of the antigen from the adjuvant inside the cell, an intracellular trigger such as reduction-oxidation (redox) potential, pH, or a specific enzyme can be used. [13][14][15][16][17][18][19] These triggers have been used in a number of devices to enhance the targeted delivery of a drug. 20,21 Triggerable formulations for immunotherapy have been investigated for intracellular targeting to APCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug binding linkers are normally designed to degrade in response to pH, enzymatic activity, light, or heat. 24 The hydrazone bond, involved in many biomolecular events, is stable at physiological Ph (7.4), yet is cleaved in acidic conditions (pH , 7.0) in a pH-dependent manner. Such a unique degradation pattern has been employed to design pH-controlled drug-delivery systems that can trigger drug release in intracellular lysosomal compartments (pH 5.0), following the cellular uptake of drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in this topic have directly benefitted from past success in the broader field of dynamic combinatorial chemistry involving reversible covalent forces to assemble new materials and devices from pools of competing subunits [12][13][14][15][16] . Only a limited number of covalent bonds have yet demonstrated sufficient reversibility to support these types of applications and most involve exchange through disulfide bonds, iminium ions, hydrazones or boronate complexes 17 . Metal-ligand interactions have also been used for exchange within dynamic mixtures 18 , and a few examples suggest that Michael reactions have a potential for reversible assembly of macromolecules as well 19,20 .…”
mentioning
confidence: 99%